Perbaikan Pengelolaan Pergudangan Melalui Penerapan Sistem Informasi Pergudangan di CV. ABB - Hery Hamdi Azwir; Oktavia Patriani (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2017)
CV ABB is a medium scale car rental company which manages around 150 vehicles consists of small car (sedan or MPV) until large bus. To supporting the maintenance of all vehicles, they build a warehouse for spareparts and tools. Unfortunately, the management of warehouse does not have a good governance because all records done manually. This situation creates very high risk for data manipulation because manual record method is done by warehouse officer, lost of spare part in warehouse, counterfeit receipt, and no system to control spare part in warehouse. An improvement need to be done by implementing a warehouse management information system to overcome this problem. By applying information system analysis and design concepts and implementing through the application of PHP7 and MySQL, the new system can control all spare part in warehouse including incoming and outgoing spare part, PIC who requests the spare part, checking stock of spare part in the warehouse and stock out used by finance to make purchase order, spare part report from supplier and spare part request report. This system is also able to help finance to create purchase order and get approval from the user in order to make the process is more transparent and accountable.